2021
DOI: 10.1177/13505076211038812
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying situated learning in organisations

Abstract: Gamification is an emerging area in research and practice that has sparked considerable interest in management studies. The attention to gamification is amplified by the ubiquitous nature of digital technologies and augmented reality which touches on how people work and learn socially. Consequently, gamified tools’ affordances affect situated learning in working environments through their implications on human relations in practice. However, the dynamics between gamification and situated learning have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 99 publications
(156 reference statements)
0
6
0
Order By: Relevance
“…The situated research context of the SETS programme displayed a strong socio-relational aspect and this ‘knowing in action’ influenced participants to share their journeys with others, to ‘know them in practice’ (Nicolini, 2013). Furthermore, it was the enactment of EL practice that drew the network of the SETS programme together, contextualising the social element in which that practice was sustained and reproduced over time in a given landscape of practice (Brown and Duguid, 2002; Spanellis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situated research context of the SETS programme displayed a strong socio-relational aspect and this ‘knowing in action’ influenced participants to share their journeys with others, to ‘know them in practice’ (Nicolini, 2013). Furthermore, it was the enactment of EL practice that drew the network of the SETS programme together, contextualising the social element in which that practice was sustained and reproduced over time in a given landscape of practice (Brown and Duguid, 2002; Spanellis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is furthermore a lack of accessibility to EL for STEM scientists since less consideration has been given to the way that learning occurs in individuals’ behaviours (Williams Middleton et al, 2014) and to developing ecosystems that encourage entrepreneurial thinking in individuals through situated learning practices (Bosman and Fernhaber, 2018; Gherardi, 2009). In addition, current literature highlights scant understanding of how, and why, scientists can embed entrepreneurial thinking in their everyday practices, in different disciplines, contexts, curriculum and geographies (Spanellis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Within this philosophical framing, we followed the approach to theorizing introduced by Furnari (2014) in AMR and subsequently showcased by Pyrko et al (2019) and Spanellis et al (2021) in Management Learning. Furnari (2014) outlines the phenomenon prior to constructing a model, rooted in the practical experience of the phenomenon and developed through theorizing, with insights illustrated by a vignette.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Pyrko et al (2019) also start from a phenomenon observed as well as described in the model of landscapes of practice (Wenger, 1998; Wenger-Trayner and Wenger-Trayner, 2014); they theorize the characteristics of the landscapes and use their thin empirical data as vignettes for showcasing their insights. Similarly, Spanellis et al (2021) start with a phenomenon described in the blog posts of a consulting company; this prompted theorizing, leading to a model, aspects of which were encapsulated in the vignettes. Like these three papers, our study starts from data that are not systematically and purposefully collected; this thin empirical material triggers phenomenal theorizing that leads to insights presented in the form of captions and descriptions.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…This positive view is endorsed also by the practitioner-oriented literature (Cross et al, 2002(Cross et al, , 2006McDermott & Archibald, 2010). In this view, CoPs achieve change mainly through modifications and improvements to work practices and increasing process efficiency through collective learning (Spanellis et al, 2021).…”
Section: The Innovating Lens: Cops As Ways Of Modifying and Improving...mentioning
confidence: 99%